2021
DOI: 10.3390/jcm10245935
|View full text |Cite
|
Sign up to set email alerts
|

Left Ventricular Lead Placement Guided by Reduction in QRS Area

Abstract: Background: Reduction in QRS area after cardiac resynchronization therapy (CRT) is associated with improved long-term clinical outcome. The aim of this study was to investigate whether the reduction in QRS area is associated with hemodynamic improvement by pacing different LV sites and can be used to guide LV lead placement. Methods: Patients with a class Ia/IIa CRT indication were prospectively included from three hospitals. Acute hemodynamic response was assessed as the relative change in maximum rate of ris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 39 publications
1
2
0
Order By: Relevance
“…Within the scope of selecting the right electrodes, the results showed that the pacing of the proximal electrode was accompanied by an increased AHR (p = 0.004) and ∆QRS area (p = 0.003). Again, this correlation did not apply for QRSd (p = 0.77) [42]. These results were confirmed in the aforementioned study by Okafor et al Also using AHR as a surrogate outcome, they found that QRS area reduction (in contrast to baseline QRS area) was significantly associated with ∆LVdP/dt max (r = −0.68; p < 0.001).…”
Section: Qrs Area In Lvlpsupporting
confidence: 68%
“…Within the scope of selecting the right electrodes, the results showed that the pacing of the proximal electrode was accompanied by an increased AHR (p = 0.004) and ∆QRS area (p = 0.003). Again, this correlation did not apply for QRSd (p = 0.77) [42]. These results were confirmed in the aforementioned study by Okafor et al Also using AHR as a surrogate outcome, they found that QRS area reduction (in contrast to baseline QRS area) was significantly associated with ∆LVdP/dt max (r = −0.68; p < 0.001).…”
Section: Qrs Area In Lvlpsupporting
confidence: 68%
“…In addition to the clinical efficacy of CRT, its cost-effectiveness has been evaluated in several analyses [ 15 , 16 , 17 , 18 , 19 , 20 ]. After reviewing literature that describes years of experience with CRT, the optimal profile of a patient who could benefit most from CRT can be specified ( Figure 1 ) [ 1 , 3 , 7 , 21 , 22 , 23 , 24 ]. Before evaluating the indications for CRT, the patient should receive optimal treatment of HF according to the current best medical knowledge for at least 3 months (or even 6–9 months) [ 1 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…The area of latest mechanical activation can be defined by echo or MRI, but this is not easily translated to implantation fluoroscopy [34,35]. The reduction in electrical dyssynchrony as assessed by reduction in vectorcardiographic QRS area could be an attractive target for lead placement strategies [36]. More simple to use would be QRS narrowing by CRT [37]; however, super-response can occur in the absence of a significant reduction in QRS duration.…”
mentioning
confidence: 99%